2011
DOI: 10.1021/jf103983m
|View full text |Cite
|
Sign up to set email alerts
|

Simple Determination of 40 Organophosphate Pesticides in Raw Wool Using Microwave-Assisted Extraction and GC-FPD Analysis

Abstract: A validated analytical method for the multiresidue analysis of 40 organophosphate pesticides (OPs) and conversion products in raw wool has been developed. The method is based on the selective microwave-assisted extraction (MAE) of raw wool with acetonitrile and analysis of extracts by gas chromatography-flame photometric detector. The optimum MAE conditions were 20 min duration at 80 °C with 30 mL of acetonitrile per gram of wool. A validation study was performed according to the European SANCO guidelines 1068… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 20 publications
(41 reference statements)
0
7
0
Order By: Relevance
“…The investigation has revealed that MAE is a more environmentally friendly process with economic advantages than the current extraction methods . MAE techniques have been developed as important means of extracting pesticides from different matrices and are gaining an important role in sample preparation .…”
Section: Introductionmentioning
confidence: 99%
“…The investigation has revealed that MAE is a more environmentally friendly process with economic advantages than the current extraction methods . MAE techniques have been developed as important means of extracting pesticides from different matrices and are gaining an important role in sample preparation .…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, our group found residues of chlorpyriphos, cypermethin, diazinon and ethion in Uruguayan lanolin samples (Pérez et al, 2010). Furthermore, when recently searching for 40 OPs residues in raw sheep wool from Uruguay, the extracted wool wax was found only containing diazinon and ethion residues (Niell et al, 2011).…”
Section: Pesticide Residues In Lanolinmentioning
confidence: 99%
“…Besides, studies in vivo and in vitro have proven that quercetin is a potential chemopreventive and chemotherapeutic agent for cancer. [28][29][30] Kaempferol (3,4 0 ,5,7-tetrahydroxy-2-phenylchromen-4-one), whose structure is shown in Fig. 1(B), has been proven by a series of pharmacological experiments to exhibit a lot of biological activities, such as resisting anxiety and oxidation, 31,32 ameliorating hyperglycemia, 33 diminishing inammation, etc.…”
Section: Introductionmentioning
confidence: 99%